PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG - Yuyun Nailufar, 09.05.51.0023 (Students Journal of Economic and Management, 2013)
This research is a study that tested the effect of leadership, workplace environment and organizational culture on job satisfaction. This study aims to examine and analyze the effect of leadership, workplace environment and organizational culture on employee job satisfaction and simultaneous partial.In this study, researchers used a sample of 100 respondents employee Politeknik Ilmu Pelayaran Semarang, the data obtained from the questionnaire. Then tested with questionnaire data validity and reliability, having obtained a valid result, then studies using multiple linear regression to describe the relationship between the variables.The result of leadership, workplace environment and organizational culture has an influence individually and collectively against employee job satisfaction. Thus, the better the leadership, work environment and organizational culture to further improve employee job satisfaction Politeknik Ilmu Pelayaran Semarang.Keywords: Leadership, Work Environment, Organizational Culture and Employee Job Satisfaction.